2013
DOI: 10.1080/03632415.2013.826201
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Genetic Identification of Spontaneously Spawned Larvae of Captive Bluefin Tuna in the Adriatic Sea

Abstract: The spawning behavior of captive Bluefin Tuna (Thunnus thynnus) was observed in cages at an Adriatic facility in summer 2011. Approximately 20,000 eggs were collected from cages and transferred to a land‐based nursery, with an estimated fertilization success rate of 80%. Eggs were spherical with a diameter of 1,035.06 ± 20.16 μm and were pelagic with a single oil globule (227.63 ± 8.07 μm). Newly hatched larvae (3.08 ± 0.14 mm total length) followed scombrid larval development: melanophores were scattered over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…This form of aquaculture activity has a range of both positive and negative impacts on marine biota within the ecosystem. Grubišić et al (2013) reported spontaneous spawning of bluefin tuna (Thunnus thynnus) during rearing practices within cages, which could possibly increase the abundance of juvenile tunas in the open sea (Džoić et al, 2017), and have a positive effect on the resilience of this species to intensive fishery exploitation.…”
Section: Interaction Of Capture-based Bluefin Tuna Aquaculture With Nmentioning
confidence: 99%
“…This form of aquaculture activity has a range of both positive and negative impacts on marine biota within the ecosystem. Grubišić et al (2013) reported spontaneous spawning of bluefin tuna (Thunnus thynnus) during rearing practices within cages, which could possibly increase the abundance of juvenile tunas in the open sea (Džoić et al, 2017), and have a positive effect on the resilience of this species to intensive fishery exploitation.…”
Section: Interaction Of Capture-based Bluefin Tuna Aquaculture With Nmentioning
confidence: 99%
“…Sampling sites included the Strait of Messina which is an important foraging area for ABFT (Battaglia et al, 2013) and where tunas are present throughout the year, raising the hypothesis that a portion of the ABFT stock might be non-migratory (Genovese, 1956;Potoschi & Sturiale, 1996). Furthermore, mitochondrial sequences of ABFT from the Gulf of Mexico (Carlsson et al, 2007) and from the Adriatic Sea (Grubišić et al, 2013) were retrieved from GenBank and analysed with the sequences obtained in the present study. Interestingly, nucleotide sequences of ABFT from the Adriatic Sea had never been investigated before in a genetic population study including ABFT samples from other geographic areas.…”
mentioning
confidence: 99%
“…AS) JX273444-JX273467(Grubišić et al, 2013) and YOY from the Gulf of Mexico (GM)(Carlsson et al, 2007) DQ 087556-DQ 087592.…”
mentioning
confidence: 99%
See 2 more Smart Citations